Efficiency of Pulsating Base Bleeding to Control Trailing Edge Flow Configurations - Carlos Carbajosa; Alejandro Martinez-Cava; Eusebio Valero; Guillermo Paniagua (Applied Sciences, 2022)
As high-pressure-turbines operate at extreme temperature conditions, base bleed can be applied at the trailing edge of the airfoils, enhancing the thermal protection along the trailing edge surface, but also disrupting the trailing edge flow and altering the overall aerodynamic pressure losses. The current work explores the potential use of base bleed as a flow control tool to modulate the flow between turbine blade rows. Through the numerical analysis of a symmetric airfoil immersed in a subsonic flow, the effects that trailing edge ejection has on the base region properties and the downstream flow are evaluated. In particular, previous research constrained to steady blowing is now extended to consider an unsteady pulsating base bleed injection. Three injection frequencies are investigated, covering a wide range of base bleed intensities. The results presented herein demonstrate that pulsating bleed flow is more efficient than its steady counterpart in terms of reducing pressure losses and controlling the primary frequency of the downstream oscillations for the same mass flow injection.